LEMBAGA ADAT MELAYU RIAU PERIODE 2012-2017 DALAM MENEGAKKAN IDENTITAS KOLEKTIF MASYARAKAT RIAU - Syu'ib "; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Customs institutions malays riau or LAM Riau has founded on 06 june 1970 with the spirit of to maintain and preserve customs malays riau. This study attempts to knowledgeable about customs institutions malays riau 2012-2017 period in enforcing collective riau identity community.This research using 7 the key informants comprising the government riau , council members riau, the DPH LAM Riau and LAM district , the private perusaahaan, the civil organitation of malays in riau and host of an organization students .This research see what customs institutions malays riau 2012-2017 period in enforcing the identity of collective riau and see faktor-faktor an impediment to enforce collective riau identity people .This research result indicates activity undertaken by lam riau in upholding collective identity masrakat riau.From this research result can be inferred customary malay institution riau saw efforts to enforce collective identity this must be supported by all parties in the form of a conservation done in direct interaction , its cultural experience , and in the form of information center that could difungsionalisasikan into the form of organising events malay culture .Keyword : Customary Malay Institution Riau, Society Collective Identity Riau